(untitled) - Hamilton, Edward A. (New York, 1996)
Newsletter Design A Step-by-Step Guide to Creative Publications "Make it dramatic. Make it readable. Make it believable." Words of advice to those who plan, design, or edit newsletters from the author of Newsletter Design, Edward A. Hamilton. Follow the advice of this designer of world-renowned publications and your newsletter will never land in the junk-mail pile. You’ll learn techniques used by the most successful publications to attract readers and rivet their attention. Included in this step-by-step guide: Planning visual content; Fast-paced journalistic writing; Forceful page layout; Eye-catching graphics; Strong, clear typography; Powerful photojournalism; Cost-wise production.
Keywords: Graphic design (Typography),Newsletters; Design